A Human Conditionally Immortalized Proximal Tubule Epithelial Cell Line as a Novel Model for Studying Senescence and Response to Senolytics - Yang, Yi; Mihajlovic, Milos; Valentijn, Floris; Nguyen, Tri Q.; Goldschmeding, Roel; Masereeuw, Rosalinde (Frontiers in Pharmacology, 2022)
Accumulating evidence suggests that senescence of kidney tubule epithelial cells lead to fibrosis. These cells secrete senescence-associated secretory phenotype (SASP) factors that are involved in diverse signaling pathways, influencing kidney fibrosis. Here, we investigated whether our previously established conditionally immortalized proximal tubule epithelial cell line overexpressing the organic anion transporter 1 (ciPTEC-OAT1) can be used as a valid in vitro model to study kidney senescence and senolytics response. To understand how permissive (33 ℃) and non-permissive (37 ℃) temperatures of the cell culture affect the senescence phenotype, we cultured ciPTEC-OAT1 for up to 12 days and evaluated the apoptosis and SASP markers. Further, the potential of navitoclax, dasatinib, quercetin and the combination of the latter two to clear senescent cells, was evaluated. Maturation of ciPTEC-OAT1 at non-permissive temperature affected mRNA and protein levels of senescence markers. A remarkable upregulation in p21 gene expression was found in the non-permissive temperature group, whereas expression of Lamin B1 decreased significantly. SASP factors, including PAI-1A, IL-1β, CTGF and IL-6 were upregulated, but no significant difference in Bcl-2 and Bcl-xl were found in the non-permissive temperature group. After culturing ciPTEC-OAT1 up to 12 days, cells in the non-permissive temperature group showed an upregulation in the apoptosis-associated proteins Bcl-2, BID and Bax and a downregulation in Mcl-1, Bad, Bak and Bim at various time points. Further, Bcl-xl, Puma, Caspase 3, Caspase 7 and Caspase 9 showed initial upregulations followed by downregulations at later time points. The loss of Lamin B1, upregulation of SA-β-gal expression and increase in its activity, upregulation of p21 levels and downregulation of p53, along with the upregulation of SASP factors, confirmed that maturation at 37 ℃ promotes senescence features. Finally, the senolytics response was evaluated by testing cell viability following exposure to senolytics, to which cells appeared dose-dependently sensitive. Navitoclax was most effective in eliminating senescent cells. In conclusion, culturing ciPTEC-OAT1 at 37 ℃ induces a senescence phenotype characterized by increased expression of cell cycle arrest and anti-apoptosis markers, SASP factors and responsiveness to senolytics treatment. Therefore, ciPTEC-OAT1 represent a valid model for studying kidney senescence by simply adjusting culture conditions.